EXAFS study of local structure contributing to Sn stability in SiyGe1-y-zSnz. (1st November 2017) - Shimura, Yosuke; Asano, Takanori; Yamaha, Takashi; Fukuda, Masahiro; Takeuchi, Wakana; Nakatsuka, Osamu; Zaima, Shigeaki
Abstract: Impact of a local bonding structure in a Siy Ge1-y-z Snz thin film on the stabilization of substitutional Sn has been investigated. Ge1-x Snx group-IV alloy is widely studied especially for optoelectronic devices as it can become a direct bandgap semiconductor material. This transition requires introduction of Sn more than its solubility limit. Although non-equilibrium growth techniques enable to incorporate a lot of Sn in Ge, attempts of Sn stabilization to prevent Sn precipitation during a fabrication process or device operation have been reported only a few. We found that Sn atom in Ge matrix can be energetically stabilized by introduction of Si and reduction of compressive strain applied from a substrate. Extended X-ray absorption fine structure study revealed that Si-Sn bond is hardly formed in the Siy Ge1-y-z Snz thin film, rather, a Sn atom locates at the 2nd nearest neighbor position of a Si atom. These results indicated that the Si-Ge-Sn local bonding structure contributes to the stabilization of Sn at a substitutional site by releasing a local strain around Sn atoms.